Community Empowerment and Student Work Together To Develop Cikoneng Village, Tangerang Regency - Joko Dewanto; Nur Azis; Vicky Hidantikarnillah; Fidiatul Adiyan (The International Journal of Education Management and Sociology, 2025)
The problems of Cikoneng village are: small and medium macro businesses do not have a business registration number, the stunting rate is quite high, the school welfare center has not been optimized, low levels of education, unemployment, lack of experts, and low capital support have resulted in a decline in the performance of the Cikoneng Village Government in Sumedang Regency. The purpose of implementing mahasiswa gotong royong membangun desa (MGRMD) at universities, local governments and communities is to have ownership in improving sustainable development goals (SDG). The community service methodology is to build harmonious interactions between educational institutions, the community, and the surrounding environment, and Community Service Program (CSP) are the application of knowledge and skills that are used to help solve problems and improve the quality of life of the people of Cikoneng Village, Sumedang Regency. The work programs carried out are: Poverty Literacy, Zero New Stunting, Puskesos, One Village One Product (OVOP), Innovation program or One Village One Innovation (OVOI). Program implementation: 1) Direct participation to the Village Government: direct cash assistance (elderly = 35 and disabled = 11), distribution of Raskin rice, recipients of additional food 7 toddlers, 2) Family assistance in the health sector: survey of high-risk pregnant women, 3) Participation in school programs: provision of anti-bullying materials in elementary schools, 4) Entrepreneurial participation: Micro, Small and Medium Enterprises (MSMEs) Cikoneng Kulon. The results are the achievement of: Zero New Stunting with the achievement of no new stunting found, One Village One Product with the achievement of successfully making fish ponds and cultivating tilapia, One Village One Innovation with the achievement of successfully cultivating maggots for waste processing and successfully making fish pellets using maggots as the basic ingredient, Extreme Community Literacy with the achievement of successfully socializing with villagers and distributing assistance together with the social service, Social Welfare Center with the achievement of successfully reactivating the village health center.